A new record and a new species of the genus Agistemus Summers (Acari: Stigmaeidae) from Greece - Stathakis, Theodoros I.; Kapaxidi, Eleftheria V.; Papadoulis, Georgios Th. (Zootaxa, 2014)
The genus Agistemus Summers (Acari: Stigmaeidae) is reported for the first time in Greece. Agistemus duzgunesae Koç, Çobanoğlu & Madanlar, a new record for the Greek fauna, is re–described and illustrated based on specimens collected from various plants. Furthermore, Agistemus macrosetosus Stathakis & Kapaxidi n. sp. is described and illustrated based on specimens collected on Rubus sp. A list of all species of the genus Agistemus is provided.